Television content in Peru: a study of the dissemination strategy of open signal channels - Atarama-Rojas, Tomás; Castañeda-Purizaga, Lucía; Londoño-Moreno, Mateo (Comunicación y Medios, 2017)
Audiovisual content has entered a new media ecosystem that requires traditional television to consider a strategy of disseminating its content through new digital platforms. In this context, the present investigation studies the case of Peru’s open signal television channels to determine how they are adapting to digital platforms. To achieve this goal, a content analysis of the traditionally broadcast programming, the website, the application, and the social networks of the channel is carried out. The results of the research reveal that most channels do not offer their content through digital platforms. Although there is an isolated case that is committed to a subscription content model. There is no interactivity and active participation of the audience in the digital platforms of the channels.